THE INFLUENCE OF STAND DENSITY AND SPECIES DIVERSITY INTO TIMBER PRODUCTION AND CARBON STOCK IN COMMUNITY FOREST - Pandu Yudha Adi Putra Wirabuana; Rahmanta Setiahadi; Ronggo Sadono; Martin Lukito; Djoko Setyo Martono (Indonesian Journal of Forestry Research, 2021)
Stand density and species diversity are two indicators that are highly related to forest productivity. However, the effect of those variables on the productivity of community forest is rarely documented. This study evaluates the influence of stand density and species diversity on timber production and carbon stock in the community forest. The study area was located in Madiun District. A field survey was conducted in four different community forest sites, i.e. Morang, Kuwiran, Randualas, and Kare. The sampling technique was by quadrat method using a sample plot size of 25 m x 25 m. The number of sample plots used in this study was 64 units, which were evenly distributed in every site. Comparison of stand attributes among sites was examined by Kruskal-Wallis test and followed by Kruskal-Nemenyi test on the effects of stand density and species diversity on timber production and carbon stock were assessed separately for each parameter using the generalized least square regression test. The process of statistical analysis was applied using a significance level of 5%. Results show a significant difference in stand volume, aboveground biomass, and carbon stock among sites (P<0.05). This study also recorded a meaningful effect of stand density and species diversity on timber production and carbon stock of community forest, wherein stand density provided a higher effect (R2 = 0.68; P<0.05) than species diversity (R2 = 0.26; P<0.05).